2005
DOI: 10.1080/03634520500213322
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the School Superintendent as Communicator

Abstract: Normative communicative behavior for school superintendents appears to have evolved as a set of role-related and context-dependent skills. The efficacy of this situational perspective, however, is questionable in relation to current conditions in society and public schools. The superintendency has evolved through four traditional conceptualizations: superintendent as a teacher of teachers, as manager, as statesman, or as applied social scientist. Experience arising from the current school reform movement demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
53
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 26 publications
3
53
0
2
Order By: Relevance
“…A review of the literature on the superintendency referenced Kowalski (2005) and his assertion that the current role of the superintendent is that of communicator, while others posited that the current conceptualization is as instructional leader. Glass and Franceschini (2007) found that half of superintendents nationally reported instructional leadership as the primary reason their boards of education hired them, representing a sharp increase from previous national studies.…”
mentioning
confidence: 97%
“…A review of the literature on the superintendency referenced Kowalski (2005) and his assertion that the current role of the superintendent is that of communicator, while others posited that the current conceptualization is as instructional leader. Glass and Franceschini (2007) found that half of superintendents nationally reported instructional leadership as the primary reason their boards of education hired them, representing a sharp increase from previous national studies.…”
mentioning
confidence: 97%
“…Early leaders were selected for their teaching expertise. Over the years, the desire for teacher expert leaders has waxed and waned as other perspectives and skills were needed, including the democratic negotiator, the evidence-based practitioner, the business expert, and the master communicator (Kowalski, 2005;Kowalski & Brunner, 2011;Moody, 2011;Sharp, Malone, Walter, & Supley, 2004).…”
Section: Implications For Superintendents As Decision Makersmentioning
confidence: 99%
“…In the current leadership landscape, there appears to be a split between leaders who lead for organizational transformation and those who lead to manage. According to education leadership scholars, the communication expertise that is required for the modern superintendent demands an ability to communicate openly, learn from the community, think about schools from a complex systems perspective, and facilitate the transformation of schools to improve education outcomes (Kowalski, 2005 (2013). At the heart of the practice of humble inquiry is the ability of leaders to both help and to be helped (Schein, 2013).…”
Section: Implications For Superintendents As Decision Makersmentioning
confidence: 99%
See 2 more Smart Citations